239 Periampullary Mixed Adenoneuroendocrine Carcinoma, Amphicrine Type: A Case Report. (11th January 2018) - Taguibao, Roberto Alvaro; Vallone, John; Lu, Di; Lu, Yuxin
Abstract: Mixed adenoneuroendocrine carcinoma (MANEC) is a rare gastrointestinal tumor with both neuroendocrine and adenocarcinoma features. It can be classified as composite (collision), combined (intermingled), or amphicrine tumor based on the distribution of the exocrine and the neuroendocrine components. When both components are coexpressed in the same tumor cells, it is classified as an amphicrine tumor, which is extremely rare. We report a 57-year-old man with hypertension presented with weakness, dizziness, and melena. CT scan showed a complex cystic mass measuring 5.8 x 5.5 x 5.0 cm abutting the duodenum with anterior displacement of the pancreatic head and adjacent inferior vena cava. The patient then received four cycles of chemotherapy with Folforinox and underwent pancreaticoduodenectomy. Gross examination showed a 7.5 x 6.5 x 5.2 cm mass with cystic and solid component located at the posterior pancreatic head and uncinate process, grossly involving the ampulla and duodenal wall, and extending into the posterior peripancreatic soft tissue. Histologically, the tumor shows conventional neuroendocrine morphology with trabecular and pseudoglandular architecture then transforms into sheets of tumor cells (which comprises 75% of the tumor), with marked nuclear pleomorphism and abundant eosinophilic cytoplasm pushing the nuclei to the periphery. Some cells have intracytoplasmic mucin and confirmed by mucicarmine stain. Immunohistochemical stains show the same tumor cells are extensively positive with neuroendocrine markers and CEA giving features of dual differentiation consistent with mixed adenoneuroendocrine carcinoma, amphicrine type. Morphologically the tumor is high grade; however, the mitotic rate and Ki67 proliferative index is low (2%). Perineural and vascular invasion is identified and one lymph node out of 16 is involved by the tumor. Because of rarity of this tumor, the clinical behavior and treatment options for amphicrine tumor remain unclear. Further investigation and study with more cases, and long-term follow-up are needed to better understand this entity.